2021
DOI: 10.1093/rheumatology/keaa840
|View full text |Cite
|
Sign up to set email alerts
|

Syndemics & syndemogenesis in COVID-19 and rheumatic and musculoskeletal diseases: old challenges, new era

Abstract: People with rheumatic and musculoskeletal diseases (RMDs) are facing several challenges during the COVID-19 pandemic, such as poor access to regular health services and drug shortages, particularly in developing countries. COVID-19 represents a syndemic, synergistic condition that interacts with and exacerbates pre-existing diseases such as RMDs, other co-morbidities and social conditions. The emerging evidence on both biological and non-biological factors implicated in worse outcomes in people with RMDs affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…Analysing also clinical and demographic data, we showed that vaccination was less attractive for patients that did not have university/college education. This is in line with a recently published study with similar setting [23], as well as with the emerging concept of "syndemics" which highlights that all aspects (including social) should be taken into account in the treatment of SRD patients, especially in the COVID-19 era [24,25]. Additionally, negative vaccination behaviour (defined here as not being vaccinated against influenza for the last 2 years), as well as nocebo-prone behaviour, has been strongly associated in our study with decreased rates of vaccination against COVID-19.…”
Section: Discussionsupporting
confidence: 87%
“…Analysing also clinical and demographic data, we showed that vaccination was less attractive for patients that did not have university/college education. This is in line with a recently published study with similar setting [23], as well as with the emerging concept of "syndemics" which highlights that all aspects (including social) should be taken into account in the treatment of SRD patients, especially in the COVID-19 era [24,25]. Additionally, negative vaccination behaviour (defined here as not being vaccinated against influenza for the last 2 years), as well as nocebo-prone behaviour, has been strongly associated in our study with decreased rates of vaccination against COVID-19.…”
Section: Discussionsupporting
confidence: 87%
“…Syndemic frameworks are one way in which this may be explored further, enabling the study of diseases using a mixed-methods approach to value the association between disease outcomes and multiple biological, psychological, social and other aspects, as demonstrated in the results of this review9 43 (figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Whether these interventions can add to or modulate the effect of DMARDs on the MetS burden needs to be established. With the advancement of the syndemics framework for complex conditions (110,111), such an approach must be conceived in this scenario.…”
Section: Unmet Needs Future Perspectives and Conclusionmentioning
confidence: 99%